Collective mobilizations in Late Republican Rome: repertoires of confrontation and interests in the ‘Ludi Romani’ (57 BC) - Moreira, Jonathan Cruz (Romanitas - Revista de Estudos Grecolatinos, 2022)
Collective mobilizations were an increasingly frequent response, in the 1st century BC, to issues that directly affected the urban plebs of Rome, especially, but not only, with regard to the price of grain. The limits imposed by the socio-political structure of the republic and the deepening of political violence at the time, deepened ties between political leaders and popular groups, so that the dependence/agency of the plebs in revolt in relation to elite leaders becomes a central aspect for understanding of this process. The main objective of this article is to reflect on the possibilities of agency in the collective mobilizations of Late Republican Rome. In order to do so, it seeks, in Charles Tilly’s concepts of confrontation repertoire, and in the case study of the Ludi Romani revolt, in 57 BC, to understand such mobilizations in their own objective interests and their practices of revolt.